Rozplanowanie wnętrz świątyni Hatszepsut w Deir El-Bahari na tle świątyń Nowego Państwa - Grabowska, Anna (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
The Hatshepsut temple is situated on the western bank of the Nile River. It followed the example of the Mentuhotep I temple from the time of the Middle Kingdom and it was the first terraced temple in the period of the New Kingdom. According to pravailing rules the initial phase of a temple complex was a lower temple located on the eastern edge of the Asasif valley. A processional alley led from the lower to the upper Hatshepsut temple. The upper temple consisted of three courtyards leading to ramps. The most important part of the temple was an upper courtyard from which all the cult places were accessible. On considering the setting of the interior of the Deir el-Bahari temple against the background of temples of the New Kingdom the fact should be noted that contrary to later erected temples in Egypt, which established strictly obeyed architectural order, the building came into being in a trial-and-error period and a period of searching for a shape which best fits cult reasons. Functionally, each part of the Hatshepsut temple answers the following elements of a classical Theban temple: pylons, (here: a stone hole in the wall), courtyards, hypostyle (here: as the columnar courtyard), the solar cult complex – so-called cult palace (here: the cult chapel of the queen and her father Totmes I), and a sanctuary. The difference between temples and their setting is the number of rooms connected with the cult. The following temples were analogous to the Hatshepsut temple in Deir el-Bahari: Totmes III temple in Deir el-Bahari and in Guma, Amenhotep II temple, Totmes IV temple near Ramesseum. In comparison with other temples of the New Kingdom the Hatshepsut temple in Del al-Bahari is an exceptional one in Egyptian architecture. Except the four mentioned temples, which refer to its terraced composition, none of later built temples has either such spatial arrangement or such an appearance. Undoubtedly its image is considerably distinguished from against the background of the other temples of the time of the New Kingdom.